2022
DOI: 10.1177/10760296221117969
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between High CHA2DS2-VASc Scores and Short and Long-Term Mortality for Coronary Care Unit Patients

Abstract: Background The CHA2DS2-VASc score has been associated with the prognosis of cardiovascular diseases. This study aimed to explore the association between the CHA2DS2-VASc score and all-cause mortality in coronary care unit (CCU) patients. Methods The study was based on the Medical Information Mart for Intensive Care (MIMIC) III database. CCU patients were divided into two groups according to CHA2DS2-VASc score: 0-3 (low risk),4-9 (intermediate and high risk). The primary outcome was 30-day mortality, and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…In agreement with several studies [ 14 – 16 ], we observed that inpatients with high CHA 2 DS 2 -VASc scores presented a significant increase in length of hospital stay and in-hospital mortality. The predictive role of CHA 2 DS 2 -VASc and mortality/length of hospital stay has been evaluated in different diseases such as myocardial infarction [ 14 ], acute pulmonary embolism [ 15 ] and in patients hospitalized with COVID-19 [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with several studies [ 14 – 16 ], we observed that inpatients with high CHA 2 DS 2 -VASc scores presented a significant increase in length of hospital stay and in-hospital mortality. The predictive role of CHA 2 DS 2 -VASc and mortality/length of hospital stay has been evaluated in different diseases such as myocardial infarction [ 14 ], acute pulmonary embolism [ 15 ] and in patients hospitalized with COVID-19 [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…Reasons for hospital readmission in AF are multifactorial and can include stroke development, bleeding progression, and concomitant disease exacerbation ( 13 ). Risk groups classified as intermediate and high CHA₂DS₂-VASc scores displayed elevated rates of comorbidities compared to those in the low-risk group, such as diabetes, hypertension, coronary heart disease (CHD), respiratory failure, hyperlipidemia, congestive heart failure (CHF), and valvular heart disease ( 14 ).…”
Section: Introductionmentioning
confidence: 99%